If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + -1 = -9y + 2 Reorder the terms: -1 + -6y = -9y + 2 Reorder the terms: -1 + -6y = 2 + -9y Solving -1 + -6y = 2 + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. -1 + -6y + 9y = 2 + -9y + 9y Combine like terms: -6y + 9y = 3y -1 + 3y = 2 + -9y + 9y Combine like terms: -9y + 9y = 0 -1 + 3y = 2 + 0 -1 + 3y = 2 Add '1' to each side of the equation. -1 + 1 + 3y = 2 + 1 Combine like terms: -1 + 1 = 0 0 + 3y = 2 + 1 3y = 2 + 1 Combine like terms: 2 + 1 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 7x-5+3x=75 | | -6-10v=-10v-6 | | w^2-2w=-67 | | -4m+7=7-4m | | 3(p-3)=24 | | -3z-10=-z+10 | | -8r-9=-8r | | 2(x-3)+5(1-x)=2 | | 11m-66-17= | | 5k-9=-9+5k | | 40(9+7x)+3-5x=17 | | 965.3616=87.92*r^2+6.28*r*9.9 | | 2-2u=-2u+2 | | -2x+-1+x= | | 8(j-4)=2(4j-3) | | 0=5b-5b | | 5(5a+2)-4a=0 | | 6x-10=5x-11 | | -2p=-p+6 | | 8(j-4)=3(4j-16) | | 5t-45= | | 0=6s-6s | | 965.3616=6.28*14*r^2+6.28*r*9.9 | | 4x^4+12x=0 | | 0=10d-10d | | 7s+11= | | 2x-5=-6m-29 | | 2+10x+18=x+4 | | -6y+23=4-7 | | 40m^2+20m=0 | | -5t=15-6t | | 3(x-4)=-5(x-4) |